2011
DOI: 10.1017/s095834401100005x
|View full text |Cite
|
Sign up to set email alerts
|

A review of multimedia glosses and their effects on L2 vocabulary acquisition in CALL literature

Abstract: This article reviews the literature of multimedia glosses in computer assisted language learning (CALL) and their effects on L2 vocabulary acquisition during the past seventeen years. Several studies have touched on this area to examine the potential of multimedia in a CALL environment in aiding L2 vocabulary acquisition. In this review, the researchers investigate the studies that deal with different modes of multimedia annotations in a CALL environment. This article reviews the empirical studies of multimedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 39 publications
(81 reference statements)
1
30
0
1
Order By: Relevance
“…This extends work by Gee (), who noted that players develop an understanding of a game's rules experientially and to the extent that they make use of various semiotic resources. This finding suggests that the embodied context of gameplay and the embeddedness of in‐game discourse in this context scaffold game‐based FL use and practice (Ibrahim, ) and is consistent with several studies in the field of multimedia glossing, which demonstrated that contextualized FL input, especially through multimodal representation, can support FL practice and learning (Hsu, Hwang, Chang, & Chang, ; Kim, ; Koolstra & Beentjes, ; Mohsen & Balakumar, ). The finding further explains the potential impact of stand‐alone gameplay on FL development (e.g., Chik, ; Ranalli, ; Ryu, ).…”
Section: Discussionsupporting
confidence: 86%
“…This extends work by Gee (), who noted that players develop an understanding of a game's rules experientially and to the extent that they make use of various semiotic resources. This finding suggests that the embodied context of gameplay and the embeddedness of in‐game discourse in this context scaffold game‐based FL use and practice (Ibrahim, ) and is consistent with several studies in the field of multimedia glossing, which demonstrated that contextualized FL input, especially through multimodal representation, can support FL practice and learning (Hsu, Hwang, Chang, & Chang, ; Kim, ; Koolstra & Beentjes, ; Mohsen & Balakumar, ). The finding further explains the potential impact of stand‐alone gameplay on FL development (e.g., Chik, ; Ranalli, ; Ryu, ).…”
Section: Discussionsupporting
confidence: 86%
“…As text-based glosses are more easily implemented and less intrusive to the comprehension processes in reading or listening than multimedia ones (Mohsen & Balakumar, 2011) and thus are commonly available and accessible in websites, the current study focuses on different gloss languages and an under-represented learner group -junior high-school EFL students. As text-based glosses are more easily implemented and less intrusive to the comprehension processes in reading or listening than multimedia ones (Mohsen & Balakumar, 2011) and thus are commonly available and accessible in websites, the current study focuses on different gloss languages and an under-represented learner group -junior high-school EFL students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, empirical studies had further investigated which types of annotations or combinations was the most effective in facilitating L2 learners' incidental vocabulary learning and text recall (see Mohsen & Balakumar, 2011;Xu 2011). The first aspect investigates which language (L1 or L2) of definition annotations better helps L2 readers learn new words and comprehend the text.…”
Section: Review Of Literaturementioning
confidence: 99%